The Use of Interactive Multimedia on Students’ Islamic Religious Education Learning Motivation - Wajdi, Muhammad Farid; Salsabila, Unik Hanifah; Prabowo, Rizky; Restiyanti, Alif Fajar (International Journal Labs, 2021)
Background: Learning media is a medium used in the learning process which includes teacher aids in teaching and is a means for students to receive learning messages. Interactive multimedia is a form of multimedia that is illustrated by the designer so that its appearance fulfills the function of informing messages and having interactive features for its users. Aim: The purpose of this study was to understand the effect of using interactive multimedia on students' learning motivation in Islamic religious education subjects. Method: The research method used was literature study and the data were generated from different relevant journal articles. Findings: The results showed that the use of interactive multimedia can develop students' learning motivation in Islamic religious education meta lessons and can improve student learning outcomes.